The Presence of Urinary Renal Progenitor Cells in Stable Kidney Transplant Recipients Anticipates Allograft Deterioration - Manonelles, Anna; Guiteras, Roser; Melilli, Edoardo; Lazzeri, Elena; Goma, Montse; Crespo, Elena; Bestard, Oriol; Sola, Anna; Romagnani, Paola; Cruzado, Josep M. (Frontiers in Physiology, 2018)
Long-term kidney transplant outcomes have reached mild improvements recently. Parietal epithelial cells (PECs) are progenitor cells located along the Bowman’s capsule that can be isolated in urine, and display the capability to replace podocytes, but in certain situations cause glomerulosclerosis. In this study, a cohort of stable kidney transplant recipients with 6-month protocol biopsy was divided in two groups depending on the presence (uPEC+; n=41) or absence (uPEC-; n=25) of PECs in urine and followed for 2 years. No differences were found between groups at 6 months after transplantation considering clinical variables, alloimmune response, renal function, albuminuria and graft pathology. However, uPEC+ group showed increased podocyturia and a higher rate of proliferating PECs along the Bowman’s capsule, without concomitant enhancement of the CD44 pro-sclerotic activation marker. Accordingly, two-year follow up evidenced poorer outcomes in the uPEC+ group with worse renal function, increased albuminuria, wider mesangial expansion and more severe IFTA. In summary, chronic allograft damage can progress in certain stable-supposed grafts by podocyte detachment and reactive PECs proliferation, being the uPEC presence a biomarker of this process. This damage-response regenerative process, if sustained in time, might fail in preserve the allograft function and histology. Our study raises new prospects to overcome current limits on long-term allograft results.